Sociedade, crítica e liberdade: um cruzamento entre as filosofias de Friedrich Nietzche e Theodor Wiesengrund Adorno - Lopes Filho, Artur Rodrigo Itaqui (Universidade do Vale do Rio do Sinos, 2008)
This essay was intended to promote, primarily, a rescue of the philosophical reflections developed by Friedrich Nietzsche and Theodor W. Adorno, obtaining from both philosophies crossover the instigation of a new debate concerning the relation between criticism and society as a principle of freedom. Therefore, it was aimed throughout four essays, the deepening of crucial subjects regarding social and cultural formation as well as the relations developed among the individuals from the modern period, at some points, exposing their reflections on contemporaneousness according to the critcal optic of the forementioned authors
Keywords: crítica; liberdade; sociedade; Theodor Adorno; Friedrich Nietzsche; criticism; freedom; society; Theodor Adorno; Friedrich Nietzsche; Ciências Humanas